The Impact of Financial Literacy, Mental Accounting, Overconfidence, and Fear of Missing Out on Investment Decisions - Miranti, Putri Kamilia (Jurnal KIAFE, 2026)
This study aims to examine the effects of financial literacy, mental accounting, overconfidence, and fear of missing out on investment decisions among individuals in Kota Pontianak. This research employs a quantitative approach using primary data collected through an online questionnaire distributed via Google Forms. The sample was selected using purposive sampling and consisted of 214 respondents aged 17 to 60 years who reside in Pontianak and have invested at least once in various investment instruments. Data were analyzed using multiple linear regression with SPSS version 29. The results show that financial literacy, mental accounting, and overconfidence have positive and significant effects on investment decisions. Meanwhile, fear of missing out has a negative and significant effect on investment decisions. Simultaneously, financial literacy, mental accounting, overconfidence, and fear of missing out significantly affect investment decisions. These findings indicate that investment decisions are shaped not only by financial knowledge and rational evaluation but also by behavioral factors, including confidence, mental categorization of money, and anxiety related to missing investment opportunities.